The perceived usability of automated testing tools for mobile applications - Hussain, Azham; Abdul Razak, Hamidah; Mkpjiogum, Emmanuel O. C. (Taylor's University, 2017)
Mobile application development is a fast-emerging area in software development.The testing of mobile applications is very significant and there are a lot of tools available for testing such applications particularly for Android and iOS.This paper presents the most frequently used automated testing tools for mobile applications.In this study, we found that Android app developers used automated testing tools such as JUnit, MonkeyTalk, Robotium, Appium, and Robolectric.However, they often prefer to test their apps manually, whereas Windows apps developers prefer to use in-house tools such as Visual Studio and Microsoft Test Manager.Both Android and Windows apps developers face many challenges such as time constraints, compatibility issues, lack of exposure, and cumbersome tools, etc. Software testing tools are the key assets of a project that can help improve productivity and software quality.A survey method was used to assess the perceived usability of automated testing tools using forty (40) respondents as participants.The result indicates that JUnit has the highest perceived usability.The study’s result will profit practitioners and researchers in the research and development of usable automated testing tools for mobile applications.